Evaluasi Efikasi dan Kontrol Locus Pengguna Teknologi Sistem Basis Data Akuntansi - Fikri Hamidy (Universitas Teknokrat Indonesia, 2017)
This research aims to empirically investigate the influences of the personality factors towards the students’ intention to use the database software at the computerized accounting vocational colleges in Lampung province. In order to answer the hypotheses, this research applies a survey study with 301 computerized accounting vocational students. Based on these samples I test using structural equation modeling of AMOS™ (Analysis of Moment Structure) software.The result of the study indicates that the estimations of the regression weights coefficient, standardized regression weights and critical ratio, has led to the conclusion that statistically, the first hypothesis is not supported whereas the second hypothesis isstatistically supported. In conclusion, , based on the low score of the standardized regression wights coefficient, it can be concluded thus, that the students’ intention to use the database software at the computerized accounting vocational colleges in Lampung Province is relatively low.Key Words : personality, intention, database software